Melayani Kristus Dengan Karya Tulis - Juanda Juanda (Sekolah Tinggi Teologi Injili Indonesia Surabaya, 2017)
The title of this qualitative study is Serving Christ In Writing. In addition through the study of literature, in this study there were five informants interviewed are in Jakarta, Bandung, and Yogyakarta 1 person and then Surabaya 2 persons. Opinion of the five informants was not too much different. Essentially a writer needs to have the preparation of the material that will be presented. But since this is within the scope of Christianity, the good news that should not be forgotten for broadcast.